Cardiac Biomarkers to Help Diagnose Cardiopathies - Correa , Ricardo; Galvis , Santiago (Spei Domus, 2014)
In the daily clinic of small animals, it is very common to find cardiac pathologies, which are diagnosed using imageology examinations like radiology, electrocardiograms and echocardiography. However, in spite of the broad researches on such techniques, it is still hard to clearly make the patient’s prognosis and objectively evaluate such pathologies. There are even patients with hidden heart diseases that may not be observed in the clinical and imageology examinations. Therefore, new methods have been studied in the past years to quickly and effectively diagnose heart diseases. Such is the case of cardiac biomarkers, like troponins and natriuretic peptides, which are more frequently used in human and animal medicine to help make the diagnosis, prognosis and evolution of heart issues in a very precisely and specifically manner. This article is intended to update the concepts on cardiac biomarkers in heart diagnosis of cats and dogs.